Research Data Publishing - Mwanzia, Leroy (International Center for Tropical Agriculture, 2018)
Data publishing involves digital dissemination of research data and supporting information such as metadata, documentation, models, code and unpublished reports in such a way that it is persistently and uniquely identifiable. In the past research data was not viewed as a central component of scholarly communication or counted as a core research output such as peer reviewed journal articles for example. However in the last number of years there is a growing emphasis of publication of research data as a principle research output. The Data Citation Principles state that “Data should be considered legitimate, citable products of research”. This seminar will look into the why, how, where and when of data publishing, from a CGIAR point of view, including an introduction to scholarly publishing through peer reviewed data papers.